2019
DOI: 10.1186/s12889-019-6853-7
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life (HRQOL) among low socioeconomic population in Malaysia

Abstract: Background The rapid growth of economy and increasing cost of living in Malaysia have given significant impact especially to the lowest household income population. The main objective of this study was to determine risk factors for low quality of life (QOL) and poor health status of this population. Methods This was a cross sectional study design. A total of 347 respondents from low household income groups, including persons with disability and Orang Asli were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 25 publications
5
44
5
2
Order By: Relevance
“…This finding is inconsistent with previous reports, which have suggested that being female is a predictor of low HRQOL in the Ethiopian communities and elsewhere [12,13,28,34]. Another report suggested that males with low SES had low HRQOL [14]. It is worth mentioning that a low percentage of female-headed household (19.30%) participated in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This finding is inconsistent with previous reports, which have suggested that being female is a predictor of low HRQOL in the Ethiopian communities and elsewhere [12,13,28,34]. Another report suggested that males with low SES had low HRQOL [14]. It is worth mentioning that a low percentage of female-headed household (19.30%) participated in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…In this work, we observed that a lower income negatively influenced physical health, which strongly supports the hypothesis that HRQOL decreases as income declines and is consistent with other previous studies [10,[13][14][15][16]. Pappa et al reported that a low income may influence physical health rather than mental health, as seen in our study [13].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Among these factors, monthly income was the strongest factor associated with not only physical HRQL but also mental HRQL, and patients with a monthly income ≥5000 Yuan showed higher HRQL scores than those of patients with a monthly income < 5000 Yuan. Indeed, personal or family income level has been previously associated with reduced HRQL in some chronic medical conditions and cardiovascular diseases [2932]. Patients with lower income may have a limited ability to obtain effective treatments, which may improve their clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%